INVESTIGATION OF THE IMPACT OF COMPRESSED NATURAL GAS ON HEAT RELEASE RATE IN DUAL-FUEL OPERATION OF A D3900 DIESEL ENGINE AT MID LOADS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
This article delves into the influence of Compressed Natural Gas (CNG) on the heat release rate of a D3900 diesel engine operating under a dual-fuel cycle, specifically at mid loads (45%). The study explores the effects of varying proportions of CNG in the total fuel supplied to the engine. Experimental investigations reveal a consistent reduction in heat release rate during dual-fuel operation, proportionate to the quantity of CNG introduced into the combustion process. Notably, the research identifies that the maximum heat release rate occurs at higher crankshaft angles. The article also contains information regarding the in-cylinder pressure and temperature when the engine operates in dual-file mode. These findings contribute valuable insights into the combustion characteristics of dual-fuel systems, shedding light on the interplay between CNG proportions and heat release dynamics in the D3900 diesel engine at mid loads.